2021
DOI: 10.1111/jdv.17381
|View full text |Cite
|
Sign up to set email alerts
|

Not all that glitters is COVID‐19: a case series demonstrating the need for histopathology when skin findings accompany SARS‐CoV‐2 infection

Abstract: Background Descriptions of cutaneous findings associated with COVID-19 have not been consistently accompanied by histopathology or confirmatory testing for SARS-CoV-2. Objective To describe and classify the cutaneous findings with supporting histopathology of confirmed COVID-19 inpatients.Methods We included consecutive inpatients with a confirmed diagnosis of COVID-19 for whom a dermatology consult was requested. A skin biopsy was performed in all cases. Skin findings were classified as being compatible with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 19 publications
0
10
0
1
Order By: Relevance
“…One reason for the misleading published data was alluded to by Kittler et al, 23 who observed that expedited peer reviews early on during the pandemic could have led to unfiltered reporting of cutaneous manifestations, whereas Vesely and Perkins 24 pertinently advised caution in the interpretation of skin findings and linked these to COVID-19. Along similar lines, Barrera-God ınez et al 25 emphasized the need for histopathologic confirmation before attributing a skin finding to COVID-19.…”
Section: Abbreviations Usedmentioning
confidence: 91%
“…One reason for the misleading published data was alluded to by Kittler et al, 23 who observed that expedited peer reviews early on during the pandemic could have led to unfiltered reporting of cutaneous manifestations, whereas Vesely and Perkins 24 pertinently advised caution in the interpretation of skin findings and linked these to COVID-19. Along similar lines, Barrera-God ınez et al 25 emphasized the need for histopathologic confirmation before attributing a skin finding to COVID-19.…”
Section: Abbreviations Usedmentioning
confidence: 91%
“…Retiform purpura and livedo racemoae have been described in severe COVID-19 with patients requiring critical level care [ 4 ••, 10 ••, 21 ]. Among cutaneous lesions, retiform purpura accounts for 6% of eruptions and occurs predominately in elderly patients with a median age of 66 [ 4 ••].…”
Section: Cutaneous Eruptions Associated With Covid-19mentioning
confidence: 99%
“…Biopsies of these lesions often demonstrate thrombotic vasculopathy with C5b-C9 complement deposition [ 4 ••, 22 ••]. These lesions were often located on the buttocks and/or the extremities [ 4 ••], though they have occurred on the trunk [ 21 ]. In a study published of 4 patients with livedoid and purpuric skin eruptions, patients developed cutaneous thrombosis and pulmonary embolisms despite the use of prophylactic anticoagulation therapy [ 22 ••].…”
Section: Cutaneous Eruptions Associated With Covid-19mentioning
confidence: 99%
“…Les mécanismes des éruptions en contexte de COVID-19 seraient l’action directe ou indirecte du virus sur la peau ou les vaisseaux, mais aussi des médicaments ou d’autres cofacteurs [ 26 ]. Les études histologiques des éruptions maculo-papuleuses ou urticariennes liées à la COVID sont peu nombreuses, les images étant compatibles avec une toxidermie ou une éruption virale [ 27 ].…”
Section: Covid Et Peauunclassified